Controlling properties of ceramic formulations for porcelain robocasting. Issue 3 (1st February 2023) - Pires, L.S.O.; Luís, J.; Fernandes, M.H.V.; Oliveira, M.
Abstract: Porcelain pastes (PlotPastes) were formulated to be used on an additive manufacturing (AM) process (material extrusion) process, primarily robocasting (R3D) technique. The material morphological and thermal characteristics were evaluated by scanning electron microscopy (SEM), differential thermal analysis (DTA) and thermogravimetric analysis (TGA). The rheology and the electrical potential of the ceramic particles were also studied to select and adequate the porcelain paste properties to the R3D AM technique. It was found that shifting the pH values to acidic, the surface charge of the particles changes and increases the pastes viscosity due to agglomeration effects. This behaviour was exploited to optimize the paste rheological behaviour which resulted in the optimum pH at 1.94 (PlotPaste 5). This paste was used in the study of R3D operating parameters. It was found that small variations in pressure and speed affects the dimensional accuracy of the printed models. The results showed the disruptive potential of porcelain R3D in the production of customized ceramic products.